Analysis of Cooperative Health Level Assessment by the Office of Small and Medium Enterprises (UKM) of North Sumatra Province - Ernida Siregar; Marliyah Marliyah (Jurnal Fokus Manajemen, 2022)
This study aims to determine the health level of the Office of Cooperatives and Small and Medium Enterprises (UKM) of North Sumatra Province and its development in 2019-2022 in terms of seven aspects, namely Capital, Asset Quality, Management, Efficiency, Liquidity, and Autonomy. and growth, and Self-Identity. This research is ia descriptive study, with the object of research being the Department of Cooperatives and Small and Medium Enterprises (UKM) of North Sumatra Province. Data analysis using a case study approach refers to the State Regulation of Cooperatives and Small and Medium Enterprises Number 14/Per/M.KUKM/XII//2009 concerning Assessment of Cooperative Health Levels. shows that the Office of Cooperatives and Small and Medium Enterprises (UKM) of North Sumatra Province: (1) Capital Aspects are at a moderately healthy level. (2) The Earning Asset Quality Aspect is at a moderately healthy level. (3) The Management Aspect is at a moderately healthy level. (4) Efficiency aspect is at moderate healthy level. (5) Liquidity aspect which is at a rather unhealthy level. (6) Aspects of Autonomy and growth are at an unhealthy level. (7) Aspect of Self-Identity is in the moderately healthy category. The development of the health level of the Department of Cooperatives and Small and Medium Enterprises (UKM) of North Sumatra Province has fluctuated. In 2019, 2020 and 2021 the Office of Cooperatives and Small and Medium Enterprises (UKM) of North Sumatra Province is in the fairly healthy category and in 2022 it is at an unhealthy level, with the average score obtained is 60.80 which is included in the healthy category currently.